Differentiation of the major flagellar antigens of Pseudomonas aeruginosa by the slide coagglutination technique. - Ansorg, R A (1984)
Antisera against the two major flagellar antigens of Pseudomonas aeruginosa were obtained by immunization of rabbits with isolated flagella and absorption of contaminating antisomatic antibodies. In the conventional slide agglutination test, the pure H antisera did not agglutinate the flagellated cells of the homologous strains. The addition of protein A-bearing staphylococci to H antiserum and homologous flagellated cells, the so-called slide coagglutination, results in a rapid development of flaky clumps. H coagglutination tests of reference strains, which formerly have been H typed by long-term tube agglutination and by the indirect fluorescent-antibody technique, yielded exactly the same subdivision of the strains in H type a and H type b as the more laborious and time-consuming methods. O grouping and H typing of 181 isolates from clinical specimens revealed a free combination of the somatic and flagellar antigens. 25 OH serovars were found. The simple and rapid coagglutination technique can promote the serovar determination of P. aeruginosa, particularly for the purpose of hospital infection control.